Palliative care provision in long-term care facilities differs across Europe: Results of a cross-sectional study in six European countries (PACE). (October 2019) - ten Koppel, Maud; Onwuteaka-Philipsen, Bregje D; Van den Block, Lieve; Deliens, Luc; Gambassi, Giovanni; Heymans, Martijn W; Kylänen, Marika; Oosterveld-Vlug, Mariska G; Pasman, H Roeline W; Payne, Sheila; Smets, Tinne; Szczerbińska, Katarzyna; et al.
Background: While the need for palliative care in long-term care facilities is growing, it is unknown whether palliative care in this setting is sufficiently developed. Aim: To describe and compare in six European countries palliative care provision in long-term care facilities and to assess associations between patient, facility and advance care planning factors and receipt and timing of palliative care. Design: Cross-sectional after-death survey regarding care provided to long-term care residents in Belgium, England, Finland, Italy, the Netherlands and Poland. Generalized estimating equations were used for analyses. Setting/participants: Nurses or care assistants who are most involved in care for the resident. Results: We included 1298 residents in 300 facilities, of whom a majority received palliative care in most countries (England: 72.6%–Belgium: 77.9%), except in Poland (14.0%) and Italy (32.1%). Palliative care typically started within 2 weeks before death and was often provided by the treating physician (England: 75%–the Netherlands: 98.8%). A palliative care specialist was frequently involved in Belgium and Poland (57.1% and 86.7%). Residents with cancer, dementia or a contact person in their record more often received palliative care, and it started earlier for residents with whom the nurse had spoken about treatments or the preferred course of care at the end of life. Conclusion: The late initiation of palliative care (especially when advance care planning is lacking) and palliative care for residents without cancer, dementia or closely involved relatives deserve attention in all countries. Diversity in palliative care organization might be related to different levels of its development.